The Voyage of the Arctic Tern - Montgomery, Hugh; Illustrated by Poullis, Nick (London Walker Books, 2002)
Narrated in verse, this is the story of skipper Bruno, cursed to a life of eternal wandering in a moment of greed and betrayal. His quest for release brings him to the court of the King of Spain and a battle with an ancient adversary, the pirate Mad Dog Morgan. Can he find redemption?
Include Illustrations.
Keywords: Pirates -- Seafaring life -- Stories in rhyme -- Adventure stories -- Voyages and travels